Economic efficiency of breeding and seed production in vegetable crops - A.N. Chuprov; D.S. Novikov; S.S. Pronin (Овощи России, 2009)
The subject of breeding and seed production has been studied as an innovative process, the result of which is new varieties and hybrids. At All-Russian Research Institute of Vegetable Breeding Production where the results of this complex system work can be exemplified. Cost efficiency of selection and seed production is analyzed, and methods of its perfection are offered. It has been proven that there is a necessity to build a State Corporation for seed production as a main link between modern economics and the seed production sector.